Particle tracking in unstructured, arbitrary polyhedral meshes for use in CFD and molecular dynamics - Macpherson, Graham B.; Nordin, Niklas; Weller, Henry G. (Communications in numerical methods in engineering, 2009)
Many classes of engineering fluid dynamics simulation require the tracking of discrete elements, for example, dispersed particles in a solvent, a spray of diesel injected into an internal combustion engine, or the dynamics of granular materials. Realistic simulations often require complex, 3D geometries, generated from CAD models and meshed with unstructured polyhedra, which may be deforming, in motion or spatially decomposed for parallel computation. We present an algorithm to track the motion of particles in such geometries which is designed to be computationally efficient and robust in imperfect 3D meshes where small holes or overlaps are present. It has been applied to a wide range of engineering problems ranging from injected fuel sprays in internal combustion engines to molecular dynamics modelling of nanoscale flows. Copyright © 2008 John Wiley & Sons, Ltd.